ANALISIS KONTRIBUSI URBAN FARMING DALAM MENDUKUNG PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) PADA PILAR EKONOMI DAN SOSIAL - Lutfiah Alfariza; Ramadhani Eka Putra; Mia Rosmiati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The increase in the number of the urban population in Indonesia raises several problems such as the increasing Open Unemployment Rate (TPT), the increasing number of poor people, and the threat to food security. These problems are certainly contrary to the goals to be achieved in the Sustainable Development Goals (SDGs). But on the other hand, there is also a phenomenon in urban Indonesia that has a positive impact on economic and social problems which means that it can also contribute to the achievement of the SDGs goals in Indonesia, namely the emergence of agricultural cultivation in urban areas or urban farming. This study aims to examine the contribution of urban farming in achieving the SDGs on the economic and social pillars, especially in goals 1 (No Poverty), goal 2 (No Hunger), goal 3 (Healthy and Prosperous Life), goal 5 (Gender Equality), and Goal 8 (Decent Work and Economic Growth). The results show that urban farming is able to increase income, provide easy access to healthy food, empower women and provide employment for urban communities. In other words, this urban farming activity makes a positive contribution to supporting the achievement of the SDGs, especially the goals of the economic and social pillars in Indonesia.